ANALYSIS OF SHARIA ACCOUNTING IN THE COLLECTION OF ZAKAT FUNDS THROUGH SOCIAL MEDIA AT BAZNAS, ENREKANG REGENCY - Sartika, Sartika; Husain, Saddan; Rismala (Institut Agama Islam Negeri Parepare, 2025)
In the ever-growing digital era, zakat management institutions are required to adapt to modern society's communication and transaction patterns. BAZNAS Enrekang Regency responds to this dynamic by utilizing social media and digital platforms as a strategic means to increase zakat collection. This research aims to identify innovations and strategies implemented by BAZNAS Enrekang in collecting zakat through social media, as well as evaluate its effectiveness in increasing muzakki participation. Using a descriptive qualitative approach, data was collected through observation, documentation, and in-depth interviews with resource persons who play a direct role in the implementation of the digitalization strategy, including social media managers and institutional leaders. The results of the study show that BAZNAS Enrekang actively uses various social media such as Instagram, TikTok, YouTube, and WhatsApp chatbots to disseminate information, zakat education, and activity reports. The use of QRIS is also an innovative solution in facilitating digital zakat payments. This strategy has been proven to be able to increase digital interaction, build public trust, and expand the reach of information. However, obstacles such as limited human resources and documentation tools are still challenges that need to be overcome. Overall, digitalization at BAZNAS Enrekang not only contributes to increasing zakat collection, but also strengthens transparency and accountability in zakat management at the regional level, making it a relevant example of adaptation in the midst of today's digital transformation.